Is Trust a Bad Investment? - Nava Ashraf; Iris Bohnet; Nikita Piankov (Center for Research in Economics, Management and the Arts (CREMA), 2004)
This paper examines whether trust is an investment decision under uncertainty, based on the expectation of trustworthiness, and whether trustworthiness is reciprocity, conditional on one's counterpart's behavior. In trust experiments in Russia, South Africa and the United States, two thirds of the subjects who trust do not expect trust to pay monetarily. We find substantial heterogeneity in motivation: Expectations of return account for most of women's trust, and reciprocity for most of Americans' trustworthiness. Men's trust and Russians' and South Africans' trustworthiness are significantly related to unconditional kindness as measured by subjects' behavior in dictator games, us ing a within-subject design.
Keywords: C72; C91; 330; Trust; kindness; reciprocity; gender; cross-cultural experiments